Debt Non-Neutrality, Policy Interactions, and Macroeconomic Stability - Ludger Linnemann; Andreas Schabert (Tinbergen Institute, 2005)
We study the consequences of non-neutrality of government debt for macroeconomic stabilization policy in an environment where prices are sticky. Assuming transaction services of government bonds, Ricardian equivalence fails because public debt has a negative impact on its marginal rate of return and thus on private savings. Stability of equilibrium sequences requires a stationary evolution of real public debt, which steers inflation expectations and rules out endogenous fluctuations. Under anti-inflationary monetary policy regimes, macroeconomic fluctuations tend to decrease with the share of tax financing, which justifies tight debt constraints. In particular, a balanced budget policy stabilizes the economy under cost-push shocks, such that output and inflation variances can be lower than in a corresponding case where debt is neutral.
Keywords: E32; E63; E52; 330; Government debt; fiscal and monetary policy rules; stabilization policy; equilibrium uniqueness; Öffentliche Schulden; Finanzpolitik; Geldpolitik; Regelbindung; Konjunkturpolitik; Theorie